Biomarkers for diagnosis and surveillance of patients with bladder cancer: a comprehensive review - Nuno Miguel Raimundo Vinagre (2020)
Bladder cancer (BC) ranks as the sixth most prevalent cancer in the world, with a steady rise in its incidence and prevalence, and is accompanied by a high morbidity and mortality. BC is a complex disease with several molecular and pathological pathways, thus reflecting different behaviors depending on the clinical staging of the tumor and molecular type. Diagnosis and monitoring of BC is mainly performed by invasive tests, namely periodic cystoscopies; this procedure, although a reliable method, is highly uncomfortable for the patient and it is not exempt of comorbidities. Currently, there is no formal indication for the use of molecular biomarkers in clinical practice, even though there are several tests available. There is an imperative need for a clinical non-invasive testing for early detection, disease monitoring, and treatment response in BC. In this review, we aim to assess and compare different tests based on molecular biomarkers and evaluate their potential role as new molecules for bladder cancer diagnosis, follow-up, and treatment response monitoring.